Chemical Characterization of Specific Micropollutants from Textile Industry Effluents in Fez City, Morocco - Hakima Talouizte; Mohammed Merzouki; Mohammed Benlemlih; Mohammed Bendriss Amraoui (Journal of Chemistry)
Textile industry is one of the most polluting industries in the world. It has a high importance in terms of its environment impact, since it consumes a considerably large amount of water and produces highly polluted discharge water. In this work, characterization of toxic organic compounds is proposed. Based on gas chromatography coupled to mass spectrometry (GC/MS) screening analysis, organic micropollutant diversity of textile effluents from a local textile processing factory was investigated. In the present work, physicochemical characterization of the studied textile effluents showed considerably high values of principal pollution parameters above the prescribed discharge water limits. Heavy metals like zinc (Zn), copper (Cu), iron (Fe), nickel (Ni), cadmium (Cd), chromium (Cr), and lead (Pb) were found to be present within the permissible limits. The results of GC/MS revealed the presence of various organic compounds belonging to a wide range of chemical classes. Main groups of chemical compounds detected in these effluents were aromatic carboxylic acids, alkanes, aromatic amines, phthalates, aliphatic carboxylic acids, and linear aliphatic alcohols. The results of this study allowed significant contributions to the chemical characterization of textile industry contaminants and identification of indicators that can be considered an important tool for assessment of the potential impact of textile activities to the contamination of aquatic environment and health hazard.